TRANSITION TO A GREEN ECONOMY: INTEGRATING NATURAL CAPITAL AND BASIC INFRASTRUCTURE INTO INDONESIA'S REGIONAL PRODUCTIVITY - Choirunnisa, Luthfi; Try Waluyo, Adiet (Salam (Islamic Economics Journal), 2026)
This study examines the dynamic relationship between natural capital, basic infrastructure, and regional economic growth in Indonesia during the post-pandemic period (2020–2024). Economic recovery following COVID-19 highlights the need to balance growth with environmental sustainability within a green economy framework. Natural capital is proxied by the Environmental Quality Index and CO₂ emissions from forest and land fires, while basic infrastructure is represented by access to clean water, roads, and electricity. Using panel data from 32 provinces, this study applies a Vector Autoregression (VAR) model, complemented by Impulse Response Function (IRF) and Variance Decomposition (VD) to capture dynamic interactions and responses to shocks. The results show that environmental quality and CO₂ emissions generate negative and persistent responses in regional economic growth, indicating the presence of a long-term trade-off between environmental conditions and economic output. Basic infrastructure also exhibits predominantly negative responses to shocks, particularly for electricity and roads, while clean water shows short-term positive but weak long-term effects. Variance decomposition results reveal that electricity access is the most dominant factor in explaining Gross Regional Domestic Product volatility. Overall, the relationship between environment, infrastructure, and growth is dynamic and highly context dependent, reflecting both structural constraints and policy inefficiency.